Bioactive 3D-Shaped Wound Dressings Synthesized from Bacterial Cellulose: Effect on Cell Adhesion of Polyvinyl Alcohol Integrated In Situ - Marlon Osorio; Jorge Velásquez-Cock; Luz Marina Restrepo; Robín Zuluaga; Piedad Gañán; Orlando J. Rojas; Isabel Ortiz-Trujillo; Cristina Castro (International Journal of Polymer Science)
We investigated wound dressing composites comprising fibrils of bacterial cellulose (BC) grown by fermentation in the presence of polyvinyl alcohol (PVA) followed by physical crosslinking. The reference biointerface, neat BC, favoured adhesion of fibroblasts owing to size exclusion effects. Furthermore, it resisted migration across the biomaterial. Such effects were minimized in the case of PVA/BC membranes. Therefore, the latter are suggested in cases where cell adhesion is to be avoided, for instance, in the design of interactive wound dressings with facile exudate control. The bioactivity and other properties of the membranes were related to their morphology and structure and considered those of collagen fibres. Bioactive materials were produced by simple 3D templating of BC during growth and proposed for burn and skin ulcer treatment.